Effects of Changing Banks' Risk Weights - Henrik Andersen; Rønnaug Melle Johansen; Knut Kolvig (Norges Bank, 2012)
The risk weights banks employ when calculating capital adequacy have been mentioned as a potential macro prudential tool to contain systemic risk emerging in specific sectors. Higher risk weights can to a certain extent mitigate systemic risk, as banks might both set aside more capital and reduce lending that generate systemic risk. In the short term, the impact of higher risk weights on credit volume will probably be moderate due to frictions in the banking sector. In the longer term, banks can pass the increased costs associated with higher risk weights on to borrowers by adjusting their lending rates. We find that a doubling of average risk weights on residential mortgage loans from the current level will probably result in a maximum rise in mortgage rates of about half a percentage point in the longer term. This may curb the rise in residential mortgage lending somewhat. Increasing risk weights on loans to the corporate sector will probably have a greater impact as products in the corporate market are more heterogeneous and banks can more easily raise lending rates. Finally, the impact on credit may be somewhat stronger if the authorities' decision to increase risk weights leads to a more conservative assessment of risk and expected return.
hdl:11250/2507187
Keywords: 330